2021
DOI: 10.3389/fmicb.2021.692313
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacillus altitudinis Strain Uses Different Novelty Molecular Pathways to Enhance Plant Growth

Abstract: The identification and use of endophytic bacteria capable of triggering plant growth is an important aim in sustainable agriculture. In nature, plants live in alliance with multiple plant growth-promoting endophytic microorganisms. In the current study, we isolated and identified a new endophytic bacterium from a wild plant species Glyceria chinensis (Keng). The bacterium was designated as a Bacillus altitudinis strain using 16S rDNA sequencing. The endophytic B. altitudinis had a notable influence on plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…Many endophytic bacteria have a broad host range. For example, Bacillus altitudinis, isolated from the wild plant species, Glyceria chinensis , can promote the growth of Arabidopsis thaliana , N. tabacum , corn, and soybean 59 . Bacillus megaterium RmBm31, an endophytic bacterium isolated from Retama monosperma , increases the biomass of A. thaliana 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Many endophytic bacteria have a broad host range. For example, Bacillus altitudinis, isolated from the wild plant species, Glyceria chinensis , can promote the growth of Arabidopsis thaliana , N. tabacum , corn, and soybean 59 . Bacillus megaterium RmBm31, an endophytic bacterium isolated from Retama monosperma , increases the biomass of A. thaliana 60 .…”
Section: Resultsmentioning
confidence: 99%
“…We observed high induction of maturase K gene expression during the interaction. Recent studies revealed that the maturase K gene is induced during the Arabidopsis-Bacillus altitudinis interaction [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific contributions of plant-growth promoting Bacillus to indirect inducible defense signaling are unknown. Bacillus altitudinis has be recorded displaying plant beneficial activity through growth promotion (seed yield and phenology) in maize ( Elfira et al, 2020 ; Zhang et al, 2021 ). Zhang et al (2021) reported maize inoculated with B. altitudinis showed increased fresh weight (g) and size ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus altitudinis has be recorded displaying plant beneficial activity through growth promotion (seed yield and phenology) in maize ( Elfira et al, 2020 ; Zhang et al, 2021 ). Zhang et al (2021) reported maize inoculated with B. altitudinis showed increased fresh weight (g) and size ( Zhang et al, 2021 ). In Miscanthus x giganteus and wheat ( Triticum aestivum ), B. altitudinis maintained biomass yield during growth in metal contaminated soils ( Pranaw et al, 2020 ; Yue et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation